2021
DOI: 10.1186/s12955-021-01829-2
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the psychometric properties of the persian version of the COVID-19-impact on Quality of Life Scale

Abstract: Introduction As a result of high transmission and mortality rates, the Covid-19 pandemic has led to a worldwide health crisis, isolation, and widespread fear, therefore negatively influencing people’s quality of life (QOL). The goal of the present study was to examine the psychometric properties (validity and reliability) of the Persian version of the COVID-19-Impact on Quality of Life (COV19-QoL) scale. Methods After translating the scale using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
3
12
1
Order By: Relevance
“…Although an important factor to study, limited number of related studies endorsed the effect of income on QoL during COVID-19 [ 28 ]. However, a study [ 15 ] that included it did not find a significant difference between different income groups in contrast to this study. However, prior research involving income and QoL relationship showed that low income is related to poor QoL [ 29 , 30 ] Increased public concern about financial conditions and economic pressure could exacerbate the pandemic influence on QoL.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Although an important factor to study, limited number of related studies endorsed the effect of income on QoL during COVID-19 [ 28 ]. However, a study [ 15 ] that included it did not find a significant difference between different income groups in contrast to this study. However, prior research involving income and QoL relationship showed that low income is related to poor QoL [ 29 , 30 ] Increased public concern about financial conditions and economic pressure could exacerbate the pandemic influence on QoL.…”
Section: Discussioncontrasting
confidence: 96%
“…In this study, the COV19-QoL scale mean ± standard deviation is 2.3 ± 0.6. However, this score is lower compared to the QoL of Iranian individuals (mean = 2.73) [ 15 ], and Filipino teachers (mean = 2.75) [ 16 ] and much lower than the score of people free from mental health problems in Croatia (mean = 2.91) [ 12 ]. Although this indicates less adverse effect on the QoL of study participants compared to others, the results of this work still suggest that the international spread of COVID-19 has definitely impacted the lives of the public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rapid transmission and increased mortality from COVID-19, governments worldwide soon implemented extraordinary measures in an attempt to contain the next pandemic [86][87][88]. The quality of life was adversely affected due to curfews, travel restrictions, and isolation measures introduced during this period [89,90]. The impact of COVID-19 on the quality of life and the increasing sense of loneliness introduced new problems and exacerbated others [91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research among dental master and doctoral students indicated that female students had lower scores on QoL [ 46 ]. On the contrary, others did not recognize the impact of gender on QoL [ 47 ]. Another study reported a lower perception of overall well-being and quality of life in students who are more emphatic about their family and friends [ 13 ].…”
Section: Discussionmentioning
confidence: 99%